OMEGA-3 AND ITS USE FOR THE PREVENTION OF PRETERM BIRTH - Martínez Velasco , Indalecio Gustavo (2024)
Preterm birth remains the leading cause of neonatal mortality worldwide, representing a persistent challenge in maternal and fetal care. Scientific evidence suggests that omega-3 supplementation can significantly reduce its incidence, especially in women with low levels of these fatty acids. This letter emphasizes the need to integrate their use into clinical practice and public health policies to improve perinatal outcomes and maternal health.